Quantitative trait loci (QTL) mapping for intermittent drought tolerance in BRB 191 × SEQ 1027 Andean Intragene cross recombinant inbred line population of common bean (Phaseolus vulgaris L.) - Nabateregga, M. (Afr J Biotechnol, 2019)
Drought is a major constraint of common bean (Phaseolus vulgaris L.) production in Uganda where irrigation for the crop is very uncommon. This study aimed to identify quantitative trait loci (QTLs) underlying drought tolerance in 128 F5 RILs derived from an Andean intra-gene cross between drought-tolerant SEQ 1027 and BRB 191. Eighteen traits were evaluated under drought stress and non-stress conditions in the field for 2 years and in the greenhouse for 1 year, respectively. A linkage map spanning 486.29 cM was constructed using 53 single nucleotide polymorphic markers (SNP) markers obtained from the KASP genotyping assay. Eleven consistent QTLs were detected on five linkage groups at a threshold of Logarithm of Odds (LOD) ≥ 3.0. Four QTLs were constitutive, seven were adaptive and were associated with 100 seed weight, grain yield, chlorophyll content, harvest index, dry weight of leaf and stem biomass and yield production efficiency. The QTL associated with a 100 seed weight (sw3.1(BS)) was the most consistent with the highest percentage of variation explained (21%). Co-localization of five drought-related factors QTLs was detected on pv10 suggesting pleiotropic effects on this chromosome. Identification of molecular markers closely linked to the QTLs identified in this study will facilitate marker assisted breeding for drought tolerance.